Philosophie der Quantenphysik : Zentrale Begriffe, Probleme, Positionen /: Zentrale Begriffe, Probleme, Positionen. (2018) - Friebe, Cord; Kuhlmann, Meinard; Lyre, Holger; Näger, Paul M; Passon, Oliver; Stöckler, Manfred
No abstract available